Kompetensi Perangkat Desa Terhadap Sistem Pengelolaan Dana Desa di Kabupaten Buleleng - I Putu Gede Diatmika; Sri Rahayu (Indonesian Publication Center, 2020)
The quality of human resources greatly affects the village fund management system. Low understanding of village fund management affects the preparation of financial reports as well as the transparency and accountability of regional financial management and village funds. Village funds can be used to facilitate and change the wheels of the rural economy through infrastructure development, improving the quality of human resources, health, village development with the aim of improving community welfare and alleviating poverty. This research is a qualitative research with a quantitative descriptive approach. A qualitative approach is a research procedure that produces descriptive data in the form of words or writings and behaviors that can be observed from the subject itself. The results of the study indicate that the competence of village officials has a positive influence on the village fund management system in the village of Panji, Buleleng Regency. The application of the village fund management system is able to present information that is relevant, clear, complete and can be justified so that the information presented is easier to understand and can be used by information users as a reference in decision making.